So sleepy story - Shulevitz, Uri, 1935- (New York : Farrar Straus Giroux, 2006)
In the quiet of the night, a sleepy sleepy boy awakes to find the dishes, chairs, and clocks enjoying themselves.
Booklist starred
School Library Journal starred
Wilson's Children
3.9
K-3.
K-3
Keywords: Night -- Juvenile fiction; Sleep -- Juvenile fiction; Night -- Fiction; Sleep -- Fiction; Night -- Fiction; Sleep -- Fiction